Approach to the Typology of Social Responsibility and its Alignment with the Organizational Culture: Analysis in the Cooperatives of Segment One in Ecuador - Torres, Sandra Patricia Galarza; Tapia, Luis Alfredo Tipán; Punina, Alvaro Patricio Carrillo; Robles, Lorenzo Adalid Armijos; Berru, Mercedes Beatriz Montero; Ochoa, Betty Elisabeth Cueva; Ortiz, Germán Gustavo Benavides (Journal of Posthumanism, 2025)
This study examines the implementation of Cooperative Social Responsibility (CSR) in 19 segment one savings and credit cooperatives in Ecuador, through a multivariate analysis that allows establishing a typology of institutional maturity around six key dimensions: cooperative governance, social, environmental, economic, ethical and technological. The methodology adopted a quantitative approach, based on Likert-type surveys applied to 2,116 employees and managers of the cooperatives analyzed. The data treatment included a cluster analysis in two phases: hierarchical (Ward) and partitional (K-means), which allowed the identification of three main clusters of CSR performance. Subsequently, an ANOVA analysis was carried out that showed statistically significant differences between the groups. The results show the existence of three levels of institutional development in CSR: (1) cooperatives with advanced and comprehensive performance in all dimensions, (2) cooperatives with consolidated but unequal practices, and (3) cooperatives in the process of systemic integration. This classification shows asynchronous trajectories within the same segment, influenced by cultural, leadership and organizational capacity factors. It is concluded that CSR in the Ecuadorian cooperative sector reflects different levels of maturity that require differentiated strategies of strengthening and accompaniment. Finally, the results generated from the typology are aligned with the theoretical dimensions of organizational culture.